Diagnostic Value of MRI Combined with CXCR4 Expression Level in Lymph Node Metastasis Head and Neck Squamous Cell Carcinoma. (8th March 2022) - Zhao, Jin; Li, Xingde; Wang, Ming; Liu, Fenghai; Wang, Jingrun
Abstract : Objective . To explore the diagnostic value of magnetic resonance imaging (MRI) combined with CXCR4 expression levels in lymph node metastasis of the head and neck squamous cell carcinoma (HNSCC). Methods . 289 patients with HNSCC were divided into lymph node metastasis group (LNM group, n = 171 ) and non-LNM group (n = 118 ) according to the pathological examination results. MRI was used to scan the patient's lesions and cervical lymph nodes, and ADC was measured by MRI diffusion weighting imaging. The expression of CXCR4 in tumor tissues was detected by qRT-PCR. Logistic regression was used to analyze the risk factors of HNSCC lymph node metastasis. ROC curve was used to analyze the diagnostic effects of MRI, CXCR4, and MRI combined with CXCR4 on HNSCC lymph node metastasis. Results . Compared with the non-LNM group, patients in the LNM group had a lower degree of pathological differentiation, and the positive rate of TNM staging and vascular invasion was higher. The signal intensity of T1WI and T2WI were low intensity and high intensity, respectively, and the ADC value was significantly reduced. At the same time, the expression level of CXCR4 in the tumor tissues of the LNM group was also significantly increased. In addition, compared with MRI and CXCR4 used alone, MRI combined with CXCR4 has a higher predictive value. Conclusion . MRI has a good effect in demonstrating lymph node metastasis. CXCR4 is significantly upregulated in lymph node metastasis tumor tissue. The combination of the two can be used for clinical diagnosis of HNSCC lymph node metastasis.